The use of direct oral challenge to confirm allergies to penicillin class antibiotics in Danish children - Thomas Krusenstjerna-Hafstrøm; Sune Rubak (BMC, 2020)
Abstract Background A high number of children are referred to pediatric departments with a suspected allergic reaction to antibiotics. The prevalence of true allergy is considered to be significantly lower than shown from clinical history and symptoms alone. This study investigated the historical use of direct oral challenges at three specialist pediatric departments in Denmark. Methods In this retrospective medical record review study, 141 children (69 boys and 72 girls) with a clinical history of suspected penicillin class allergy were investigated. A standardized questionnaire for drug allergy was completed in the beginning of the investigation, which also included a skin prick test (SPT), measurement of IgE to different types of penicillin, and a drug challenge (DC). Results Only four (2.8%) of the patients referred for further investigation in our study had a positive DC. We found no correlation between a positive DC, positive SPT or elevated specific IgE. None of the patients with a positive DC reacted with a rash alone prior to investigation. Conclusions Allergy to penicillin in children is rare and probably overestimated. In children reacting to penicillin with a rash alone, our study indicated that the rash was probably not related to allergy and treatment should thus be continued.